The Implementation of Rural Tourism Development Policy at Kampung Adat Cireundeu - Rachmawati, Emi; Dyah Khatamisari Rachaju, Rannie; Alamianti, Dina; Suhara, Ero (International Journal of Psychosocial Rehabilitation, 2020)
Adat village, as a nation’s asset, can be developed as a tourism potential that nurtures from local wisdom. Its development depends on dynamic dimension growth that attracts domestic and international tourists. The development management of rural tourism, with a particular and intense local wisdom, must be maintained by qualified human resources that are capable of regulating local wisdom with information technology development. Therefore, this research aims to analyze and comprehend the rural tourism development’s policy implementation at Kampung Adat Cireundeu. The impediment factor and subsidiary factors, as well as the chairman of the culture, tourism, youth, and sports department, effort in rural tourism policy implementation. This research used the qualitative method. Thus, data were obtained through participant observation, in-depth interviews, and documentation. The Miles and Huberman model is used as a data analysis technique. This research concludes that policy implementation of rural tourism at Kampung Adat Cireundeu has several impediment factors, such as the constraints of infrastructure development, undeveloped tourism attractions packages, and networking cooperation. The subsidiary factors are not well managed. But not to eliminate the efforts on overcoming the barriers in policy implementation that apprehend the development of rural tourism that is advanced at the moment.